If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -5x + 1 = -65x + 36 Reorder the terms: 1 + 11x + -5x = -65x + 36 Combine like terms: 11x + -5x = 6x 1 + 6x = -65x + 36 Reorder the terms: 1 + 6x = 36 + -65x Solving 1 + 6x = 36 + -65x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '65x' to each side of the equation. 1 + 6x + 65x = 36 + -65x + 65x Combine like terms: 6x + 65x = 71x 1 + 71x = 36 + -65x + 65x Combine like terms: -65x + 65x = 0 1 + 71x = 36 + 0 1 + 71x = 36 Add '-1' to each side of the equation. 1 + -1 + 71x = 36 + -1 Combine like terms: 1 + -1 = 0 0 + 71x = 36 + -1 71x = 36 + -1 Combine like terms: 36 + -1 = 35 71x = 35 Divide each side by '71'. x = 0.4929577465 Simplifying x = 0.4929577465
| 3(2x-3)-(4x-5)=0 | | 3x-11=75-5x | | 2x-3=7(x-2)4 | | 3*3-3*3=2 | | 5-5=5X+4X | | 5*9+5*4=280 | | 10W-17W=-49 | | -3-5=-6+X | | 3x(2)+7=5(3x+4) | | 3x+4*5=6 | | 3(x+9)(x-7)=0 | | -4x=17-5 | | A+(n-1)d=45 | | (x^2)+20x=800 | | (3xy+3)(5x^3y^2+2)=0 | | T^3-4t=-3 | | -5-7=10x+5-9x | | 196-14x=98-7x | | 4(2-1)-66=-5(2x+3) | | (-x+5)(7x-14)=0 | | 60x=x-3x | | -5x-2=x+4 | | 90-4x=2x+8 | | 4x+2.5=12.5+2x | | 35+x=14 | | 4x+2.55=12.5+2x | | -11x-4=14-9x | | 23-3n= | | 8+9x=134-12x | | 4096-x=127 | | x^4+2=-5 | | 272p-6=9p+5 |